Presenting "pissis girls": Categorisation in a social media video. (June 2015) - Halonen, Mia
Abstract: In Finland, a social category called "pissis girls" has evolved into a cultural concept, used widely in various discourses concerning young women. In the paper, the empirical focus is on how, in the context of a viral video disseminated in social media, a group of young girls are presented as representatives of this category. The video, called ÄM IRK, is a short edited clip of an emergent interaction between young men and girls meeting by chance in a park. Drawing on the notions of membership categorisation, cluster of indexes and indexical field, "enoughness" and authentication, the paper investigates how the edited video, through the means of de- and recontextualisation of the emergent interaction evokes the category of the pissis girls in the ways in which it represents young adolescent girls. More specifically, the paper shows how the edited video uses selected emblems and activities that have been interpreted as key indices of the pissis category, such as the use of alcohol and the appearance and vanity of the girls, as semiotic material evocative "enough" to make the category of pissisness salient. Furthermore, in order to categorise someone as an authentic pissis girl, one has to show how the girls deviate from the ones who are not, that is, the "ordinary" or "good" or "appropriate" girls. And, in turn, when some emblems and activities are considered bound to the pissis girl category, the norms concerning girls in general become visible. In the video, the dynamics of categorisation, authentication, and normativity merge.